THE INFLUENCE OF LIFESTYLE ON THE EFFICACY AND SAFETY OF MEDICATIONS IN CARDIOLOGICAL PRACTICE: WHAT SHALL PHYSICIAN BE AWARE OF? - E. I. Tarlovskaya; N. A. Koziolova; A. I. Chesnikova (Российский кардиологический журнал, 2016)
The article provides an overview of the data on the influence of food, herbs, alcohol and smoking on the efficacy and safety of drug treatments. It is shown, that strictly implausible is to take drug treatments and fitomedicines at the same time, those influencing metabolism in opposite ways. Alcohol consumption, depending on duration and intensity, also influences the effectiveness of drugs. The compounds of tobacco smoke significantly decrease the effectiveness of many medications, activating cytochrome systems. While choosing the medications, it is important to prefer those drugs having minimum interactions with food as with drugs.